Utilização de modelo de referência para a melhoria dos processos construtivos de edificações buscando a redução da geração de resíduos no setor de construções residenciais - Pasa, Carine Cristiane Machado Urbim (2012)
The construction industry produces large amount of waste during the execution of their projects and the cause of this generation is often related to the way of executing the construction processes tasks. In most businesses there is no formalization of the production process and problems such as design changes, inadequate specification of materials, execution errors and lack of planning contribute to this situation. The production process in construction is characterized by constant production cycle of new developments, changes in process during the development of the work, the production process is organized by project, little interaction between team members design and product development period quite variable. In this research it was used the Fractal Clover Reference Model to map the production process in construction of residential buildings in order to propose best practices to reduce waste generation. The application process of the reference model is an interactive and iterative process, the choice of starting point for its application is random and depends on the case which is being analyzed. The approach to the problem was qualitative and employed as a technical field research with an exploratory descriptive. Data collection was through interviews with engineers, workers and observations in residential construction in Ponta Grossa city. It was observed that the two main causes of waste generation are the errors involved in project activities and implementation of projects. Regarding to projects, the main flaws are the lack of compatibility and design changes during the execution of the project. During the task execution, the generation of waste is related to errors during the performance of activities due to worker’s lack of qualification and lack of planning and management of the implementation of the project. The application of the Fractal Clover Reference Model showed as best practices the compatibility of projects, the transfer of information and feasibility of the project to the client, the qualifications of the workforce and proper management and planning for the implementation of enterprise.